2015
DOI: 10.1038/srep16094
|View full text |Cite
|
Sign up to set email alerts
|

Administration of defined microbiota is protective in a murine Salmonella infection model

Abstract: Salmonella typhimurium is a major cause of diarrhea and causes significant morbidity and mortality worldwide, and perturbations of the gut microbiota are known to increase susceptibility to enteric infections. The purpose of this study was to investigate whether a Microbial Ecosystem Therapeutic (MET-1) consisting of 33 bacterial strains, isolated from human stool and previously used to cure patients with recurrent Clostridium difficile infection, could also protect against S. typhimurium disease. C57BL/6 mice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 58 publications
0
35
0
Order By: Relevance
“…Defined gut microbial species have been shown to maintain tight junction integrity, which in turn limits Salmonella typhimurium invasion. 88 Gut microbiota promote the secretory IgA response that inactivates rotavirus and neutralises cholera toxin, 87 and outcompete C. difficile colonisation thereby preventing infection. 47 Key gut microbial species also prime the development of cellular immune responses in the GI tract.…”
Section: Infectious Diseasesmentioning
confidence: 99%
“…Defined gut microbial species have been shown to maintain tight junction integrity, which in turn limits Salmonella typhimurium invasion. 88 Gut microbiota promote the secretory IgA response that inactivates rotavirus and neutralises cholera toxin, 87 and outcompete C. difficile colonisation thereby preventing infection. 47 Key gut microbial species also prime the development of cellular immune responses in the GI tract.…”
Section: Infectious Diseasesmentioning
confidence: 99%
“…Intriguingly, the in vitro increase in keratinocyte transepithelial electrical resistance (TER) induced by a B. longum lysate, but not by an L. rhamnosus GG lysate, was abrogated in the presence of a TLR2-neutralizing antibody, suggesting that these bacteria act on different pathways to influence tight junction molecule expression (185). An in vivo infectious model recently demonstrated that a defined mixture of 33 probiotic bacterial strains pre- vented the Salmonella enterica serovar Typhimurium-induced disruption of ZO-1 and claudin-1 in mice and ameliorated disease severity (191).…”
Section: Other Mechanisms Of Action Of Beneficial Microbes and Probiomentioning
confidence: 99%
“…MET-1 also attenuated TcdA-mediated apoptosis, another factor known to contribute to loss of gut barrier integrity [45], and enhanced tight junction protein expression. MET-1 has been shown to protect the expression of tight junction proteins important in the maintenance of host barrier function in an antibiotic-associated colitis animal model using Salmonella typhimurium [23], a pathogen that does not depend on toxin production for its pathogenicity. Of interest, MET-1 also preserves tight junction protein expression and attenuates systemic and local inflammation in a DSS mouse model of colitis [63].…”
Section: Discussionmentioning
confidence: 99%
“…A score between 1 and 3 was assigned for each parameter, and the overall score was the sum [22]. Immunofluorescence staining of myeloperoxidase (MPO) and claudin-1 was carried out on formalin-fixed cecal tissues as previously described [23]. …”
Section: Methodsmentioning
confidence: 99%